RATIONAL PHARMACOTHERAPY IN PEDIATRICS AND RUSSIAN NATIONAL PEDIATRIC MEDICATION GUIDELINES - A.A. Baranov; V.K. Tatochenko; L.S. Namazova; G.A. Samsygina; K.I. Saitkulov (Педиатрическая фармакология)
.